INVESTIGATING THE ELEMENT OF CRIMINAL JUSTICE IN THE LIGHT OF INTERNATIONAL CRIMINAL COURTS - Ashkan Famil Modaberan, Seid Mehdi Salehi, Reza Nikkhah Sarnaghi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Universal jurisdiction of criminal law is one of the important principles in determining jurisdiction of states and criminal law. According to this principle, any country may prosecute and punish an offender without prejudice to his or her nationality in respect of the offender’s or nationality’s crime, place of crime or the interests of the injured State. . In the twentieth century, several specialized international criminal courts were formed on a case-by-case basis in connection with the burden of numerous international crimes. The parallel and symmetrical jurisdiction of these courts clearly identifies the relationship between national courts and international criminal courts. All international documents and domestic laws have recognized these rights and spoken about them in various places. On the other hand, protecting the rights of the citizen in the process of justice demands that every person be brought to justice for the wounded so that the accused can be comforted and hopes for a fair trial in the fullest sense. At the international level, criminal authorities Permanent and occasional are good options for using the international community to fight international crime. Therefore, the International Criminal Court is the only permanent and competent jurisdictional authority for dealing with international crimes, but some restrictions, such as the need to refer the situation of international crimes to the Security Council, preclude achieving that goal which we have discussed this in this article.